Anxiolytic medication use is not associated with anxiety level and does not reduce complications after acute myocardial infarction. Issue 11 (12th January 2013) - Abed, Mona A; Frazier, Susan; Hall, Lynne A; Moser, Debra K
<x xml:space="preserve">Abstract</x> Aims and objectives To examine the association of anxiety level and anxiolytic medication use with in‐hospital complications in patients following acute myocardial infarction (AMI). Background There are conflicting data about the protective effect of anxiolytic medication used in patients after acute myocardial infarction. Examination of the interaction of anxiolytic medication and anxiety level may explain these disparate results. Design This was a secondary analysis of existing data from a multisite, prospective study of the impact of anxiety on in‐hospital complications in patients with AMI. Methods Patients were primarily men, Caucasians, with Killip class 1 or 2, from the USA and Australia (n = 156). Anxiety level in the emergency department and intensive care unit and in‐hospital complications were collected using self‐report measures and medical record review. Logistic regression analyses examined whether the use of anxiolytic medication influenced the relationship between anxiety and in‐hospital complications after controlling for demographic and clinical covariates. Results In the ED, 31% of participants were very or extremely anxious; anxiolytic medication was given to only 5%. In the intensive care unit, nearly half of participants received anxiolytic medication. There was no association between anxiety level and use of anxiolytic medication. Anxiety was an independent predictor of the probability of in‐hospital complications. The administration of anxiolytic medication did not alter the relationship between anxiety and in‐hospital complications. Conclusion Use of anxiolytics in patients with AMI was not associated with anxiety level and did not reduce the probability of in‐hospital complications. Relevance to clinical practice Clinicians need to regularly assess anxiety and treat it appropriately. Regular anxiety assessment may promote appropriate use of anxiolytic medication. Clinical guidelines for the management of patients with an AMI should address anxiety assessment and appropriate use of anxiolytic medication to improve patients' outcomes.